Stability Study of Flat Hull Ship for Fishing Tourism - Nabawi, Rahmat Azis; Syahril, Syahril; Salmat, Salmat (Teknomekanik, 2020)
The availability of boats is needed to develop fishing tourism. Most of the boats used so far generally use fishing boats made of woodcut in the forest, so this can damage the environment and cause natural disasters. Ships using a flat plate hull made of steel can be a substitute for wooden ships. This study aims to test the stability of a flat plate vessel designed for fishing boats. The ship stability test was carried out using a computer simulation method using Maxsurf Stability software. The ship stability criteria refer to the International Maritime Organization code A.749 (18), Ch 3-design criteria applicable to all ships. The ship stability analysis was carried out on two variations of the load case. The value of GZ at A h 300, A h 400 and A h 300 - A h 400 for load case 1 and 2 are greater than the minimum standards determined by IMO. The maximum GZ value at load case 1 occurs at an angle of 400 and at load case 2 at an angle of 60.90. The GM value in load case 1 is 0.609 meters and in load case 2 is 0.485 meters. Based on the results of the tests that have been carried out, it can be denied that the flatboat design model for fishing tourism meets the criteria set by the International Maritime Organization.